2015
DOI: 10.1371/journal.pntd.0003831
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Schistosomiasis and Soil-Transmitted Helminths in Namibia: The First Large-Scale Protocol to Formally Include Rapid Diagnostic Tests

Abstract: BackgroundNamibia is now ready to begin mass drug administration of praziquantel and albendazole against schistosomiasis and soil-transmitted helminths, respectively. Although historical data identifies areas of transmission of these neglected tropical diseases (NTDs), there is a need to update epidemiological data. For this reason, Namibia adopted a new protocol for mapping of schistosomiasis and geohelminths, formally integrating rapid diagnostic tests (RDTs) for infections and morbidity. In this article, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Treating trace results as positive may result in over-treatment; however, in low transmission areas, if there is sufficient praziquantel available, this may be preferable to under-treatment for achieving elimination. Souza-Figueiredo et al (40) showed that, in a low transmission setting (prevalence below 10%), the urine CCA test performed better if the observer considered trace results as negative cases. If trace results are considered to represent positive cases, the test becomes more sensitive but also, as a consequence, less specific.…”
Section: Resultsmentioning
confidence: 99%
“…Treating trace results as positive may result in over-treatment; however, in low transmission areas, if there is sufficient praziquantel available, this may be preferable to under-treatment for achieving elimination. Souza-Figueiredo et al (40) showed that, in a low transmission setting (prevalence below 10%), the urine CCA test performed better if the observer considered trace results as negative cases. If trace results are considered to represent positive cases, the test becomes more sensitive but also, as a consequence, less specific.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple factors that can significantly increase the risk of infection with schistosomes might be important drivers for the existence and persistence of schistosomiasis transmission hot-spot areas and their resilience to PC and other intervention measures such as snail control and health education. These risk factors include living in close proximity to a freshwater body containing intermediate host snail species [17, 21, 24], frequent and intense contact of humans with natural freshwater [17, 25], lack of drinking water sources and latrines in schools [25] and the construction of agricultural water schemes [26]. Also “super-spreaders”, potentially untreated or treated and then re-infected people that harbour heavy infections, might contribute to the perpetuation or resurgence of transmission [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Souza-Figueiredo et al 110 previously reported that POC-CCA® results are more in agreement with those of K-K when traces are considered negative in low-endemic areas. This is not considered in Brazilian studies, however, even if a reference method is adopted.…”
Section: Performance Of Circulating Antigen-based Rdt Diagnosis In Lomentioning
confidence: 58%